Do incumbents manipulate access to finance during banking crises? - Feijen, Erik, 1977- 1977- (Policy research working paper, 2005)
"The author tests the hypothesis that during systemic banking crises, access to finance is opportunistically tightened by incumbents to eliminate or weaken competition from mainly young firms. He finds this to be especially true in more corrupt countries. To do so, he uses a methodology similar to Rajan and Zingales (1998) on three-digit manufacturing industry-level data provided by the United Nations Statistics Division for about 15 industrial and developing countries in over 20 industries on average. The author shows that price-cost margins in externally more financially dependent industries are higher during crisis than in externally less dependent industries in countries with higher levels of corruption. He finds the opposite relationship for the change in the industry-level number of establishments during a crisis. The results withstand an array of robustness checks, including using different indices of corruption, different controls, and robust estimation techniques. "--World Bank web site